THE EFFECT OF WORK MOTIVATION, CLASSROOM MANAGEMENT AND CRITICAL THINKING SKILLS TOWARDS TEACHERS’ COMPETENCE IN INQUIRY-BASED LEARNING - Mely Kartono (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2021)
This research is a quantitative study using path analysis, which aims to measure the effect of work motivation, classroom management and critical thinking skills towards teachers’ competence in IBL. The subjects involved in this study are 34 teachers at XYZ School. Data collection was obtained by distribution of questionnaires as primary data, analyzed using SmartPLS. Interviews and observation using checklist as secondary data were also recorded to observe data triangulation. The research was conducted on 28th March 2016 until 1st April 2016. The results obtained are that work motivation, classroom management and critical thinking skills has an effect of -0.619, 0.409, and -0.174 towards teachers’ competence in IBL respectively. Work motivation has an effect of 0.082 and 0.147 towards classroom management and critical thinking skills respectively. Critical Thinking Skills has the strongest effect of 0.708 towards Classroom Management.